UPAYA BPSDMD PROVINSI SUMATERA SELATAN DALAM MENINGKATKAN KEMAMPUAN WIDYAISWARA MEMBUAT KARYA TULIS ILMIAH (KTI) - Lamazi, Lamazi (Publikasi Penelitian Terapan dan Kebijakan, 2019)
The purpose of this study is to describe: the obstacles of Widyaiswara in BPSDMD South Sumatra Province in making Scientific Papers, improving the ability to do Scientific Writing, and the efforts undertaken by BPSDMD South Sumatra Province in increasing Widyaiswara's ability to make Scientific Writing. This study uses a qualitative approach with phenomenological design. Data collection uses interviews, observation, and documentation. Data validity techniques in this study use triangulation of sources and techniques. Data analysis uses interactive models with the process of data collection, data reduction, data presentation, and conclusions. The results of this study arebarriers to Widyaiswara BPSDMD of South Sumatera Province in making Scientific Writing constrained by time, reference, meet the style of the publisher's environment and limited facilities and lack of motivation,and also ability to make it through training, reading books and other journals, asking friends, attending workshops/seminars and try continuously, efforts made by BPSDMD of South Sumatra Province in improving the ability of widyaiswara in doing Scientific Writing in general, are divided into four types as follows: provide administrative support, financial support, opportunities to Widyaiswara in order to allocate time, energy and costs for making scientific papers, conducting technical guidance for making Scientific Papers.